The influence of social isolation and COVID-19 on high-performance athletes (Research, Society and Development, 2022)
Objective: To analyze the influence of Covid's isolation period and contagion on training, pace, performance and injuries in high-performance athletes. Methodology: This is an observational, descriptive, cross-sectional and quantitative study. Inclusion criteria: athletes who were linked to a federation and of both sexes. Exclusion athletes were athletes who did not respond adequately to the form. A form was made with the athletes about their socioclinical data and questions related to Covid-19, isolation, return to training, performance and injuries, after which a descriptive analysis of the collected data was carried out. Results: The sample was formed by a total of 37 athletes, 62.2% returned out of pace and with low physical conditioning after isolation; 64.9% did not suffer any injuries when returning from training. Regarding the confirmed diagnosis of COVID-19, 21.6% of players were infected, of which 50% stated that COVID-19 had a moderate influence, needing a period of more than a month to return to the performance and pace of before. Final considerations: The present study did not reveal any causal evidence about the impact of the isolation and contagion of COVID-19 in relation to the number or risk of injuries. However, some influences on performance, rhythm and physical conditioning were evidenced.